Beyond the Rhetoric: Analysis of the Experienced Journey of Diversity Awareness - Lott de Araújo, Luiza; Silva Custódio, Luciana; Ferreira Gonçalves, Ana Paula; Naessa Gonçalves Miranda, Amanda (Revista del CLAD Reforma y Democracia, 2025)
Diversity plays a transformative role in building fairer, more innovative, and more productive work environments. This article explores the initiatives promoted by the government of Minas Gerais through the Transforma Minas Program, highlighting the importance of intersectionality and inclusion in public management. Based on data from the social security census, which covered more than 130,000 active public servants, it examines structural inequalities and the efforts to combat them, especially in the leadership sphere. The methodological approach includes the description of concrete actions, such as the review of selection processes and management tools, and the analysis of data that reveal disparities in gender, race, and other social markers. By proposing public policies that go beyond rhetoric, the program reaffirms the State’s commitment to equity, to social justice, and to the reduction of inequalities. It is concluded that practical and continuous actions are needed to promote significant changes in the work environment and public service, benefiting both public servants and society as a whole, while reaffirming the role of the government as an agent of social transformation.
Keywords: diversity; government initiative; sociodemographic data; representativeness; people management